Recommended abbreviations for the names of genera of the phylum Tardigrada - Perry, Emma; Miller, William R.; Kaczmarek, Łukasz (Zootaxa, 2019)
When listing the tardigrade species found in a study, the general practice is to sort the list alphabetically or taxonomically by genus. The first time a genus name is used it is spelled out and then it is abbreviated with the first letter of the genus followed by a full stop (period) until a different genus is encountered. This practice works for both a paragraph and a table listing and has been used by tardigrade researchers as far back as Schultze (1834). In the last monograph, Ramazzotti & Maucci (1983) presented a listing of the 52 generic abbreviations they used. We present an updated list of unambiguous abbreviations consistent with the International Code of Zoological Nomenclature (ICZN) for the now 137 recognized tardigrade genera.